Secondary cardiocerebral infarction after acute inferior myocardial infarction treated with two emergency thrombectomies: a case report - Dong, Ming-Zhen; Zhu, En-Bo; Lin, Ming-Quan; Dong, Guang-Hui; Jin, Guang-Lin; Qu, Lin-Zhuo; Che, Hui-Ying; Guan, Hong-Jian (Frontiers in Medicine, 2025)
Acute myocardial infarction (AMI) and acute ischemic stroke (AIS) are among the leading causes of disability and mortality worldwide. Cases of acute ischemic stroke secondary to acute inferior myocardial infarction are exceedingly rare in clinical practice, leaving physicians with limited experience and lacking established guidelines for management. This report presents the case of an elderly female patient who was admitted with acute inferior myocardial infarction. During conservative management, she subsequently developed two episodes of acute ischemic stroke, both of which were treated with emergency endovascular thrombectomy, and she ultimately recovered and was discharged.